(untitled) (Journal of Renal and Hepatic Disorders, 2020)
Pre-transplant kidney biopsy is routinely used to decide whether kidneys from marginal donors should be transplanted as single or double trans-plantation. This is a 5-year extension of the follow-up of a previous study. In that study, graft outcomes were compared retrospectively between a group of 44 recipients of a single kidney graft from an extended criteria donor and a Karpinski histological score of ≤3, and another group of 56 recipients of a single transplant with a Karpinski histological score of 4 or 5. After 5 years of transplantation, there was no difference between the two groups in terms of recipient’s serum creatinine levels (1.8 ± 0.5 vs 1.9 ± 0.6 mg/dL, P = 0.5), creatinine clearance (53 ± 23 vs 49 ± 27.0 mL/min, P = 0.6), or the rates of graft loss (41% vs 49%,P = 0.5). Therefore, the choice between single and double transplant should not be made only on the basis of histological score but should be done together with the evaluation of donor’s clinical parameters, especially the renal function.